AICCRA Ghana Accelerator Programme: Strengthening Public–Private Partnerships for Scaling Bundled Climate-Smart Solutions - Yeboah, Stephen; Dalaa, Mustapha Alasan; Obeng Adomaa, Faustina; Mahama, Obed Kwaku; Tepa Yotto, Ghislain (2025)
The reports presents partnership between the District CSA Hubs and Scaling Accelerator Consortia partners which has created a multi-level, public–private ecosystem that accelerates the delivery and adoption of CIS-CSA innovations. The report shows how the collaboration enables rapid diffusion of innovations across multiple communities and districts, stronger institutional coordination and ownership at the local government level, greater commercial viability of CSA technologies through private-sector involvement, and socially inclusive and gender-responsive scaling pathways. These together enabled farmers to access and use climate smart solutions which improved their resilience and productivity. Ultimately, the integration of district-led coordination and private-sector innovation has allowed AICCRA to achieve scaling with depth and sustainability, ensuring that climate-smart solutions reach the farmers who need them most while building long-term institutional capacities within Ghana’s agricultural system.